2022
DOI: 10.1155/2022/8133970
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Purple Mashua Extracts Using Andean Tuber Starches Modified by Octenyl Succinic Anhydride

Abstract: This work is aimed at optimising the spray drying conditions of the phenolic extracts of purple mashua microencapsulated with octenyl succinic anhydride (OSA) Andean tuber starches. Purple mashua extracts were obtained and spray dried using native and OSA starches of yellow oca, pink oca, and yellow olluco (140°C, 4% starch). The powders obtained were analysed by encapsulation efficiency of anthocyanin (EE), total phenol content, and antioxidant capacity to select the best starch for optimisation purposes. OSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…It can be observed that an increase in temperature leads to a significant increase in polyphenols. This phenomenon can be attributed to the almost instantaneous formation of a protective layer of gelatinized starch on the nanocapsules due to a higher inlet temperature in the spray-drying process [4,60]. On the other hand, it can be seen that a higher percentage of encapsulants is associated with a significant decrease in the concentration of these compounds.…”
Section: Nanoencapsulation Of Phenolic Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be observed that an increase in temperature leads to a significant increase in polyphenols. This phenomenon can be attributed to the almost instantaneous formation of a protective layer of gelatinized starch on the nanocapsules due to a higher inlet temperature in the spray-drying process [4,60]. On the other hand, it can be seen that a higher percentage of encapsulants is associated with a significant decrease in the concentration of these compounds.…”
Section: Nanoencapsulation Of Phenolic Compoundsmentioning
confidence: 99%
“…The increase in temperature could be attributed to the destabilization of the nanocapsule walls, facilitating the release of bioactive compounds [4]. However, increasing the concentrations of the encapsulating agents reduced the antioxidant activity, a behavior related to the decrease in the content of bioactive compounds due to the dilution effect of the matrix [60].…”
Section: Nanoencapsulation Of Phenolic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations